The Perfect Performance of Tariqat Al-Mutakallimin According Fakhrudin Al-Razi Perspective - Nasiri Nasiri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Fakhr al-Din al-Razi is a great scholar who controls various branches of science, especially Islamic sciences. In almost every branch of science studied, he wrote one or more works which some of them became the main references, such as the book al-Mahsul fi 'Ilm al-Ushul and Tafsir al-Kabir Mafatih al-Ghaib. Although he was a follower and defender of the Shafi'i school in the field of fiqh and the Ash'ari school in the field of kalam, but his mastery of knowledge was so broad and deep and his critical thinking about various sciences actually demonstrated his capabilities as a mujtahid. His main work in the field of ushul fiqh, namely al-Mahsul, is the best work that brings together four master books in the field of ushul al-fiqh tariqat al-mutakallimin from its predecessors. He succeeded in presenting ushul al-fiqh comprehensively more than his predecessor, including Imam Shafi'i himself. The analytical-critical description provides a depth of understanding of the various things discussed in the book. Although his work is seen as a result of the merger of the four previous books of ushul al-fiqh, but his analyzes and some opinions show the independence and originality of the writer's thinking.